Placing ‘The once and future king’ - Johnson, Flint F. (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
This article is a survey of the sites normally associated with Arthur followed by an exploration as to why they were originally connected with him. It begins with the Arthurian battles listed in Historia Brittonum. Following is a discussion on Camlann. After that, the sites commonly associated with Arthur’s capital are listed and their political, literary, or religious reason for first being linked with Arthur are given. Southern Wales, Somerset, Caerleon, Celliwig, Winchester, and Carlisle are all explored in the essay. Keywords: Arthur; Arthurian location; Arthurian sites; Historia Brittonum; Annales Cambriae; Y Gododdin